2019
DOI: 10.1097/md.0000000000017853
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two-thumb encircling and two-finger technique during infant cardiopulmonary resuscitation with single rescuer in simulation studies

Abstract: Background:The recommended chest compression technique for a single rescuer performing infant cardiopulmonary resuscitation is the two-finger technique. For 2 rescuers, a two-thumb-encircling hands technique is recommended. Several recent studies have reported that the two-thumb-encircling hands technique is more effective for high-quality chest compression than the two-finger technique for a single rescuer performing infant cardiopulmonary resuscitation. We undertook a systematic review and meta-analysis of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
3
9
2
Order By: Relevance
“…Systematic reviews suggest that the 2-thumbencircling hands technique may improve CPR quality when compared with 2-finger compressions, particularly for depth. 42,43 However, recent manikin studies suggest that the 2-thumb-encircling hands technique may be associated with lower chest compression fractions (percent of cardiac arrest time that chest compression are provided) 44 and incomplete chest recoil, 45,46 especially when performed by single rescuers. See Figure 3 for the 2-thumb-encircling hands technique.…”
Section: The Optimum Compression-to-ventilation Ratio Ismentioning
confidence: 99%
“…Systematic reviews suggest that the 2-thumbencircling hands technique may improve CPR quality when compared with 2-finger compressions, particularly for depth. 42,43 However, recent manikin studies suggest that the 2-thumb-encircling hands technique may be associated with lower chest compression fractions (percent of cardiac arrest time that chest compression are provided) 44 and incomplete chest recoil, 45,46 especially when performed by single rescuers. See Figure 3 for the 2-thumb-encircling hands technique.…”
Section: The Optimum Compression-to-ventilation Ratio Ismentioning
confidence: 99%
“…Two CPR pilot tests on the mannequins, including the two-hand CC method for adults and the two-thumb CC method for infant, confirmed that the smart ring can be used to estimate CC depth. Comparing the two-finger and the two-thumb CC methods for infants, several studies have reported that the two-thumb CC method is more effective [ 18 , 19 ]. The reason is that the two-finger method is difficult to fix the CPR posture compared to the two-thumb method.…”
Section: Discussionmentioning
confidence: 99%
“…For infants (<1 year), only the so-called two-thumb-encircling technique with the thumbs on top of each other (Figure 2) is recommended as this is associated with a better compression quality and less fatigue than the two finger technique which is no longer advised for trained rescuers or healthcare providers. 20 Placing the thumbs on top of each other (rather than next to each other) is advised based on weak evidence suggesting a higher perfusion pressure and lesser compression of the liver. The technique for thorax compressions in older children with one or two hands has not changed.…”
Section: Thorax Compressionmentioning
confidence: 99%